Kepemimpinan Visioner Dalam Membangun Komunitas Belajar Kolaboratif - Muh Ibnu Sholeh (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
This research to analyze the challenges in integrating visionary leadership and collaborative learning communities, as well as analyzing the impact of collaborative learning communities on teacher performance. The method used in this research is descriptive qualitative. Data is collected through written sources such as relevant journals and books. The data analysis carried out was descriptive analysis, by looking for patterns and finding themes that emerged from the materials collected. Data analysis techniques go through the stages of data collection, data presentation, data condensation and drawing conclusions. The research results found that challenges in integrating visionary leadership and collaborative learning communities include differences in approach and focus, the need for commitment and involvement, conflict in decision making, managing change, and a focus on outcomes and processes. The impact of collaborative learning communities on teacher performance includes improving teaching skills, using innovative approaches, increasing creativity, increasing self-reflection, emotional support and motivation, increasing connectedness with students, providing constructive feedback, increasing a sense of ownership of work, increasing positive attitudes. employment relations, and improving student academic achievement